Keeping the beat against time: Mitochondrial fitness in the aging heart - Mendoza, Arielys; Karch, Jason (Frontiers in Aging, 2022)
The process of aging strongly correlates with maladaptive architectural, mechanical, and biochemical alterations that contribute to the decline in cardiac function. Consequently, aging is a major risk factor for the development of heart disease, the leading cause of death in the developed world. In this review, we will summarize the classic and recently uncovered pathological changes within the aged heart with an emphasis on the mitochondria. Specifically, we describe the metabolic changes that occur in the aging heart as well as the loss of mitochondrial fitness and function and how these factors contribute to the decline in cardiomyocyte number. In addition, we highlight recent pharmacological, genetic, or behavioral therapeutic intervention advancements that may alleviate age-related cardiac decline.